1982
DOI: 10.2337/diacare.31.12.1044
|View full text |Cite
|
Sign up to set email alerts
|

Increased Peripheral Insulin Sensitivity and Muscle Mitochondrial Enzymes but Unchanged Blood Glucose Control in Type I Diabetics After Physical Training

Abstract: Nine male, insulin-dependent diabetic patients participated in a 16-wk training program consisting of 1 h of jogging, running, ball games, and gymnastics, performed 2-3 times/wk. The training resulted in an 8% increase of maximal oxygen uptake (P less than 0.01). Insulin sensitivity as determined by the insulin clamp technique increased 20% (P less than 0.05). Glycosylated hemoglobin showed no change (10.4 +/- 0.7% versus 11.3 +/- 0.5%), 24-h urinary glucose excretion was not reduced, and home-monitored urine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
2

Year Published

1985
1985
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(43 citation statements)
references
References 15 publications
3
38
2
Order By: Relevance
“…The lack of improvement of glycemic control is consistent with previous results showing that physical activity does not automatically improve glycemic control in patients with DM1 in the absence of a controlled diet [37][38][39][40]. Blood lipids did not improve after two and four months of training and no association with ADMA could be found.…”
Section: Discussionsupporting
confidence: 93%
“…The lack of improvement of glycemic control is consistent with previous results showing that physical activity does not automatically improve glycemic control in patients with DM1 in the absence of a controlled diet [37][38][39][40]. Blood lipids did not improve after two and four months of training and no association with ADMA could be found.…”
Section: Discussionsupporting
confidence: 93%
“…One of the unique features of mammalian skeletal muscle is its remarkable ability to adapt to altered functional demands by changing these phenotypic profiles (8,46). Various stimuli including innervation/neuromuscular activity, mechanical loading/unloading, physical activity, or even hormonal levels and aging can trigger alterations in various functional components, including contractile protein elements, proteins of oxidative phosphorylation, as well as the vasculature (22,26,27,29,41,45). More recently, genetic engineering-mediated manipulation of expression of functional proteins has also been shown to induce phenotypic adaptation in skeletal muscle (23), providing mechanistic clues to the tightly regulated physiological structure in and around myofibers as an integrative unit for function.…”
mentioning
confidence: 99%
“…Aerobic exercise training from 12 to 16 weeks, 3-4 times per week for at least 60 min resulted in improved insulin sensitivity or TDD reduction in patients with T1DM [40][41][42]. A recent meta-analysis of six randomized trials (323 adults) found that aerobic or resistance exercise twice weekly for a minimum of 2 months led to a significant HbA1c reduction of 0.78 % (95 % CI : 0.41,1.14) and improved cardiorespiratory fitness while insulin dose reduction of 0.4 units/kg was reported in one study but not the others [43•].…”
Section: Diet and Exercisementioning
confidence: 99%